Разведки 2009 г. в Черноморском р-не Автономной республики Крым - Храпунов, И.Н.; Смекалова, Т.Н.; Столба, В.Ф. (Археологічні дослідження в Україні, 2010)
The publication is devoted to the archaeological prospecting at the Tarkhankut peninsula in the Crimea during which a lot of sites of the Late Bronze Age and the Hellenistic period were examined.